Unveiling the Space Weather During the Starlink Satellites Destruction Event on 4 February 2022 - Tong Dang; Xiaolei Li; Bingxian Luo; Ruoxi Li; Binzheng Zhang; Kevin Pham; Dexin Ren; Xuetao Chen; Jiuhou Lei; Yuming Wang (Space Weather)
Abstract On 4 February 2022, 38 Starlink satellites were destroyed by the geomagnetic storm, which brought significant financial, aerospace and public influences. In this letter, we reveal the space weather process during 3–4 February 2022 geomagnetic disturbances, from the Sun all the way to the satellite orbiting atmosphere. Initiated by an M1.0 class flare and the following coronal mass ejection (CME), a moderate geomagnetic storm was stimulated on 3rd February by the CME arrival at Earth. Subsequently, another moderate storm was triggered on 4th February by the passage of another CME. Model simulations driven by solar wind show that the first geomagnetic storm induced around 20% atmospheric density perturbations at 210 km altitude on 3rd February. The unexpected subsequent storm on 4th February led to a density enhancement of around 20%–30% at around 210 km. The resulting atmospheric drag can be even larger, since the regional density enhancement was over 60% and the satellite orbits were continuously decaying. This event brings forth the urgent requirements of better understanding and accurate prediction of the space weather as well as collaborations between industry and space weather community.